Safeguarding the patient: a grounded theory study of registered nurse anesthetists' main concerns in the process of extubation in the anesthesia setting - Linda Rönnberg; Christina Melin-Johansson; Ove Hellzén; Ulrica Nilsson; Marie Häggström (BMC, 2022)
Abstract Background The process of extubation is complex as it takes place in the technical and challenging environment of the operating room. The extubation is related to complications of varying severity and a critical moment for the patient, who is in a vulnerable condition when emerging from anesthesia. Registered Nurse Anesthetists (RNAs) in Sweden have specialist training and performs extubations independently or in collaboration with an anesthesiologist. Aim To obtain a deeper understanding of Registered Nurse Anesthetists' main concerns and how they resolve these in the process of extubation when caring for a patient during general anesthesia. Participants A total of 17 RNAs, eight male and nine female, were included in the study. Twelve RNAs in the first step of data collection (I); and five RNAs the second step of data collection (II). Method A classic grounded theory approach with a qualitative design was used for this study. Findings The RNAs' main concern in the process of extubation were Safeguarding the patient in a highly technological environment, which the solved by Maintaining adaptability. Facilitators as well as challenges affected how the RNAs solved their main concern and represented the categories: 'Having a back-up plan', 'Getting into the right frame of mind', 'Evaluating the patient's reactions', 'Using one's own experience', 'Dealing with uncertainty', 'Pressure from others', and 'Being interrupted'. The theory, Safeguarding the patient in the process of extubation, emerged. Conclusion To be able to safeguard the patient in a highly technological environment, the RNAs must oscillate between facilitators and challenges. By maintaining adaptability, the RNAs resolved the difficulties of oscillating, indicating a need for finding a balance between maintaining attentiveness on what is important to keep the patient safe in the process of extubation and all of the disturbances present in the OR.